Optimalisasi Rancangan Potensi Desa Wisata Oleh UMKM Lokal Di Desa Gedangan Kecamatan Mojowarno Kabupaten Jombang - Achmad Syaifulloh Putra; Arya Gilang Wiryawan; Rosedefi Angelia Putri; Sarah Adora Febria; Virda Kurnia Barbara; Dhian Satria Yudha Kartika (Politeknik Kampar, 2023)
Small Micro Medium Enterprise (Usaha Kecil Mikro dan Menengah or UMKM) are one of the driving factors of the economic condition of a region. Gedangan Village, Mojowarno District has the potential for local UMKM whose management has not been optimized to improve economic conditions in the village. Optimizing UMKM management can be done by designing the potential of tourist villages by local UMKM through digital branding. This is done with the aim of strengthening the marketing and branding of UMKM in Gedangan Village. The stages carried out in designing tourism by local UMKM in Gedangan Village, namely 1) Data collection of local UMKM, 2) UMKM marketing strategy training, 3) UMKM assistance, 4) UMKM registration on Google, 5) Designing local MSME tourism through Instagram, and 6) Assistance also evaluation with the Gedangan Village Government.